PENATALAKSANAAN FISIOTERAPI PADA KASUS FROZEN SHOULDER ETCAUSA KAPSULITIS ADHESIVA MENGGUNAKAN MODALITAS SWD, TERAPI MANIPULASI, DAN TERAPI LATIHAN DI RSUD BANDUNG KIWARI - Angelika Wirani; Lona Thesalonika; Ika Rahman (Jurnal Infokes, 2022)
Frozen Shoulder et causa Adhesive Capsulitis is a shoulder joint condition characterized by pain and limited movement that can interfere with daily activities. This study aimed to assess the effectiveness of a combination of physiotherapy modalities, namely Short Wave Diathermy (SWD), manipulation techniques, and exercise therapy in treating this case. Using a descriptive design with a case study approach, this research was conducted on a 54-year-old male patient at Bandung Kiwari Hospital. Evaluation was performed using Visual Analog Scale (VAS) to measure pain levels, goniometer to measure range of motion (ROM), and Shoulder Pain and Disability Index (SPADI) to assess disability levels. After 6 therapy sessions, the results showed a significant decrease in pain levels on the VAS measurement scale, increased ROM based on goniometer measurements, and a 25% decrease in SPADI score in terms of movement disability. These results indicate that the combination of SWD modalities, manipulation, and exercise therapy is highly effective in reducing pain, improving ROM, and enhancing shoulder function in cases of Frozen Shoulder et causa Adhesive Capsulitis.